THE EFFECT OF RED LED LIGHTS ON POT CATCHES IN PENAAH WATERS, LINGGA RIAU ISLAND: Pengaruh Penggunaan Lampu LED Merah Terhadap Hasil Tangkapan Bubu di Perairan Penaah, Lingga Kepulauan Riau - Saputra, Riki; Mawardi, Wazir; Riyanto, Mochammad (Bogor Agricultural University, 2023)
Pot fisheries are one of the dominant activities of capture fisheries in the Penaah waters of Lingga, Riau Archipelago. This study aims to determine the effect of red LED lamp attractors on the fish catches of pots and identify the fish species. This study was conducted in the waters of Pena'ah Village, Senayang District, Lingga Regency, Riau Islands, using an experimental method. Data were collected from 18 pots for 18 days. There were three treatments, namely pot without using bait as a control, pot with red LEDs light, and pot with red LEDs light and bait, in which a total of six units of pots on each treatment. The pots caught 18 groupers during the study, of which nine individuals were captured by the pot with a red LED and bait, five individuals by the pot with a red LED pot, and four individuals without bait. The effectiveness analysis showed that the pot with red LED and bait was the highest (50%), the pot with red LED had a value of 28%, and the lowest was trapped without bait with an effectiveness value of 22%. The total catches of the pot based on the economic fish showed that adding a red LED attractor gave more types of catch than control. The red LED attractor is expected to be a solution to increase the effectiveness of the pot.